Investigating grade 4 learners' enactment of utterances embodied in a mathematical classroom discourse - Mokwana, Tebogo Abie (My University, 2023)
The study aimed to investigate Grade 4 learners’ enactment of utterances embodied in mathematical classroom discourse. I adopted teaching experiments as a design for the study and I observed learners’ utterances and interactions in their attempts to develop mathematical knowledge; hence I adopted a teaching experiment design. I designed the research process, and engaged with and reported on all 73 Grade 4 learners in the classroom. The learners were grouped in groups of four in order for them to engage with each other and with me. Furthermore, I only questioned and guided learners when they were learning in groups. In teaching experiment design, the researcher’s role is to organise, listen and observe and, in this study, I organised, listened to and observed the learners, who I viewed as ‘students of mathematics’. I collected data by making use of observations, interviews, video recordings and notetaking to capture learners' interactions among themselves and with my. Furthermore, I used preliminary and retrospective analysis, as prescribed by the teaching experiment design (Steffe & Thompson, 2000). As a result, I captured the results from each teaching episode and analysed the learners’ interactions preliminarily. Afterwards, I returned to the teaching episodes and analysed the learners' interactions in order to undertake a retrospective analysis. I used tenets of the dynamic system theory of cognitive development to analyse the interactions.The key findings from the study were that learners portray different utterances depending on the concept of engagement. These utterances influenced their learning of mathematical concepts. The positive utterances that learners portrayed enhanced their development in mathematical thinking. On the other hand, negative utterances did not influence the development of learners’ mathematical thinking. Furthermore, learners portrayed positive utterances when engaged in questions involving mathematical shapes and negative utterances when engaged in word problems
Thesis (M.Ed. (Mathematics Education)) -- University of Limpopo, 2023
Keywords: Grade 4 learners; Mathematical classroom discourse; Mathematical knowledge; Mathematics -- Study and teaching; Education; Education, Primary -- South Africa